Economic Activity and Pollution:The case of Indonesia 1967-2013 - Mohammad Rofiuddin; Tito Aditya Perdana; Nugroho SBM (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2017)
Increased economic activity accompanied with environmental pollution. The objective of the study was to analyze the effect of per capita GDP on CO2 emissions and to prove the hypothesis of the Kuznets environment curve. Method for analyzing data by using multiple linear regression with quadratic equation. The results show that GDP per capita has a positive and significant influence on CO2 emissions, as well as the square GDP per capita has a negative and significant influence on CO2 emissions, so the Kuznets Environment Curve's hypothesis can be proven.